Molecular Systems Biology of Neurodevelopmental Disorders, Rett Syndrome as an Archetype - Faundez, Victor; Wynne, Meghan; Crocker, Amanda; Tarquinio, Daniel (Frontiers in Integrative Neuroscience, 2019)
Neurodevelopmental disorders represent a challenging biological and medical problem due to their genetic and phenotypic complexity. In many cases, we lack the comprehensive understanding of disease mechanism necessary for targeted therapeutic development. One key component that could improve both mechanistic understanding and clinical trial design is reliable molecular biomarkers. Presently, no objective biological markers exist to evaluate most neurodevelopmental disorders. Here we discuss how systems biology and 'omic' approaches could address the mechanistic and biomarker limitations in these afflictions. We present heuristic principles for testing the potential of systems biology to identify mechanisms and biomarkers of disease in the example of Rett syndrome, a neurodevelopmental disorder caused by a well-defined monogenic defect in MECP2. We propose that such an approach can not only aid in monitoring clinical disease severity, but can also provide a measure of target engagement in clinical trials. By deepening our understanding of the “big picture” of systems biology, this path could even help generate hypotheses for drug development programs, hopefully resulting in new treatments for these devastating conditions.